CONCEPTUAL MODEL OF TRAINING BACHELORS OF PHYSICAL CULTURE AND SPORTS FOR COACHING ACTIVITIES IN GAME SPORTS WITH PRESCHOOL CHILDREN - Ihor Bohdanovskiy (Scientific Journal of Polonia University, 2023)
The article analyzes the current state of research on the problem of training bachelors of physical culture and sports for coaching activities in game sports with children of preschool age, which confirmed the relevance and expediency of the chosen problem, its insufficient theoretical development in pedagogical theory and practice. The following structural components of the training bachelors of physical culture and sports for coaching activity in game sports with preschool children are defined and characterized: motivational-value, informational-communicative, organizational-facilitating, reflective-creative. A conceptual model has been developed, which provides for an integral continuous process of training bachelors of physical culture and sports for coaching activities in game sports with children of preschool age. The model covers four interconnected blocks: the target one, which reflects the social order of society, the goal, the task of training bachelors of physical culture and sports for coaching activities in game sports with preschool children and its components; the methodological block of the model is built according to the principles and requirements for training bachelors of physical culture and sports for coaching activities with preschool children. This block is based on methodological approaches (system, activity, competence, person-oriented, environmental, synergistic, simulation- game) and principles (the principle of integrity, the principle of structuring, the principle of conscious creative activity, the principle of professional orientation, the principle of individual self-worth, the principle of relying on subjective experience of students, the principle of partnership, the principle of complex interaction, the principle of freedom of choice, the principle of novelty); of content containing the principles, organizational and pedagogical conditions of training bachelors of physical culture and sports for coaching activity with preschool children, forms and methods used in this process; the resultant block contains components (motivational- value, informational-communicative, organizational-facilitating, reflective-creative), criteria (motivational, cognitive, activity, analytical), levels (high, sufficient, low) of training of bachelors of physical culture and sports motivation for coaching activities with preschool children. It was found that the training of bachelors of physical culture and sports for coaching activity with preschool children becomes effective thanks to the implementation of the following organizational and pedagogical conditions: promotion of the formation of bachelors of physical culture and sports motivation for coaching activities of teaching sports games of preschool children; actualization of interdisciplinary integration and its scientific and methodological support in the process of training bachelors of physical culture and sports for coaching activities in teaching sports games of preschool children; provision of practice-oriented training of bachelors of physical culture and sports for coaching activities in teaching sports games of preschool children through the involvement of stakeholders in the educational process, the interrelationship of competence, system and personal-activity approaches.